Horn Fly (Diptera: Muscidae)—Biology, Management, and Future Research Directions. Issue 1 (27th October 2021) - Brewer, Gary J; Boxler, Dave J; Domingues, Luisa D; Trout Fryxell, Rebecca T; Holderman, Chris; Loftin, Kelly M; Machtinger, Erika; Smythe, Brandon; Talley, Justin L; Watson, Wes
Abstract: The horn fly, Haematobia irritans irritans (L.), is one of the most important external parasites of cattle in North America and elsewhere. Horn fly adults have an intimate association with cattle, their primary host. With their often-high numbers and by feeding up to 38 times per day per fly, horn flies stress cattle. The resulting productivity loss is valued at more than 2.3 billion USD in the United States. Insecticides are commonly used to mitigate direct injury from feeding and indirect injury from disease transmission. This paper discusses horn fly biology, distribution, and management. Emphasis is on promising new approaches in novel insecticides, repellents, biological control, vaccines, animal genetics, and sterile insect technology that will lead to effective preventative tactics and the integration of smart technologies with horn fly management. We conclude with a discussion of research needs necessary to shift horn fly integrated pest management to an emphasis on preventative tactics and the precision use of reactive techniques.